The Relationship Between Gestational Diabetes, Emotional Eating, and Clinical Indicators - Yildirim, Tugce Tasar; Akcabay, Cigdem; Yildiz, Sevler; Kutluer, Gulsen (Mdpi, 2025)
Background and Objectives: Gestational diabetes mellitus (GDM), which is becoming increasingly common in contemporary society, is recognized for its considerable psychosocial impact on pregnant women throughout the perinatal phase. The purpose of this research was to explore the possible links between mental health status and dietary habits among pregnant women diagnosed with GDM, alongside examining how these factors correlate with clinical indicators like HbA1c measurements and the necessity for insulin therapy. Materials and Methods: The study included 82 pregnant participants, 37 with gestational diabetes mellitus and 45 without. Blood samples were collected from all participants for biochemical analysis, including fasting blood glucose, postprandial blood glucose, and HbA1c levels, which can be clinical indicators for the presence of gestational diabetes mellitus, and the need for insulin treatment was recorded. Then, participants completed a questionnaire collecting sociodemographic and clinical data as well as the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Salzburg Emotional Eating Scale (SEES), and REZZY Eating Disorders Scale (REZZY). Data were statistically analyzed. Results: A previous diagnosis of gestational diabetes was more frequent in the case group (18.9%) than in the control group (2.2%) (p = 0.020). OGTT positivity was detected in 56.8% of the case group, whereas all control participants had negative results (p < 0.001). There were no statistically significant differences between the two groups in psychological symptom scores or eating behavior assessments (p > 0.05). Conclusions: Pregnant women with gestational diabetes mellitus were observed to score higher on measures of anxiety, depression, and emotional eating, particularly in response to negative emotions. These findings may indicate a potential association between gestational diabetes and psychological or behavioral factors related to metabolic regulation during pregnancy.
Keywords: gestational diabetes mellitus; anxiety; depression; eating disorders